The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0210865
|View full text |Cite
|
Sign up to set email alerts
|

Describing vegetation characteristics used by two rare forest-dwelling species: Will established reserves provide for coastal marten in Oregon?

Abstract: Forest management guidelines for rare or declining species in the Pacific Northwest, USA, include both late successional reserves and specific vegetation management criteria. However, whether current management practices for well-studied species such as northern spotted owls (Strix occidentallis caurina) can aid in conserving a lesser known subspecies—Humboldt martens (Martes caurina humboldtensis)–is unclear. To address the lack of information for martens in coastal Oregon, USA, we quantified vegetation chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Although shrub cover was lower in seasonally-flooded shore pine forest, seasonal flooding may have contributed to the relative absence of bobcats and other competitors there, perhaps conferring some competitive advantage to the scansorial marten if they are able to travel through the canopy more readily when forests are flooded (Fig 6). Although shrubs were not prevalent in all forests used by martens, other studies in the Pacific states have shown strong association with shrub cover and therefore further mechanistic studies examining whether shrubs provide protective cover may be warranted [12,65].…”
Section: Discussionmentioning
confidence: 99%
“…Although shrub cover was lower in seasonally-flooded shore pine forest, seasonal flooding may have contributed to the relative absence of bobcats and other competitors there, perhaps conferring some competitive advantage to the scansorial marten if they are able to travel through the canopy more readily when forests are flooded (Fig 6). Although shrubs were not prevalent in all forests used by martens, other studies in the Pacific states have shown strong association with shrub cover and therefore further mechanistic studies examining whether shrubs provide protective cover may be warranted [12,65].…”
Section: Discussionmentioning
confidence: 99%
“…We removed marten locations from our model sample that occurred in areas that disturbance (fire or harvest) between the data of observation and the date represented by our vegetation layers (2016). If there were multiple locations within the 500-m cell, we spatially-thinned locations prioritizing those in the order of: (1) rest and den locations from telemetry studies in the Central Coastal Oregon population (Linnell et al 2018) and the Northern Coastal California population (Delheimer et al In press; PSW 2019); (2) locations from scat dog detection surveys (Rogue Detection Teams, Rice, WA; Conservation Canines, University of Washington, Seattle, WA) from both Oregon populations (detailed methods within Moriarty et al 2018; Moriarty et al 2019); and (3) locations from baited camera and/or track plate surveys from all four populations in Oregon (Barry 2018; Moriarty et al 2019) and California (Gamblin 2019; Slauson et al 2012). We thinned locations to one within a 500-m cell, attempting to maximize distances between locations and induce spatial independence for modeling (Kramer-Schadt et al 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Humboldt martens ( M. c. humboldtensis ) are a subspecies of Pacific marten that historically occurred throughout coastal forests of northern California and Oregon. Contemporary range-wide surveys suggest that distribution of Humboldt martens is substantially reduced compared to historical representations (Moriarty et al 2019; Zielinski et al 2001). Consequently, Humboldt martens were listed as Endangered under the state of California’s Endangered Species Act (CDFW 2019) and as threatened under the federal Endangered Species Act as a “coastal distinct population segment of Pacific martens” (USFWS 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations